KINERJA ASOSIASI PENGELOLA SISTEM PENYEDIAAN AIR MINUM DAN SANITASI (SPAMS) PERDESAAN “SUMBER BATHORO KATONG” KABUPATEN PONOROGO TAHUN 2019 - Nur Wahyudi; Qomaruddin Qomaruddin; Joko Pramono (Master of Public Administration, Universitas Slamet Riyadi, 2020)
Ponorogo District mission carried out by the Departement of Public Works,Housing and Settlement Area one of them is to arrange a comfortable area for all,with the availability of adequate public space, environmentally friendly, as well asefforts to accelerate the reduction of inequality between rural and urban areas.One of which is done is by Rural Sistem Penyediaan Air Minum (SPAM)development activities. After the completion of the Rural SPAM developmentactivities, requires organization to manage the SPAM. SPAM managers isHimpunan Penduduk Pemakai Air Minum (HIPPAM) and Badan PengelolaSistem Penyediaan Air Minum dan Sanitasi (BP-SPAMS). To strengthen theorganizational capacity of The HIPPAM and BP-SPAMS, in 2018 formed AsosiasiPengelola Sistem Penyediaan Air Minum dan Sanitasi (SPAMS) Perdesaan“Sumber Bathoro Katong” Kabupaten Ponorogo for The 2018 – 2023. ThisAssociation is a government partner and other concerned parties related to thedelivery of community based drinking water and sanitation services in thePonorogo District. The Association aims to support increasing coverage ofdrinking water and sanitation services to 100%, increasing the capacity of villageleveldrinking water and sanitation managers and facilitating partnership activitieswith District Governments and Village Governments, the private sector(Corporate Social Responsibility / CSR) and other actors. Although TheAssociation has been formed for more than a year, and has a large task andfunction; but The Association's performance is not yet optimal. The performanceof The Asosiasi Pengelola Sistem Penyediaan Air Minum dan Sanitasi (SPAMS)Perdesaan “Sumber Bathoro Katong” Kabupaten Ponorogo in 2019 based onperformance indicators according to Robbins (2006: 260) is as follows.Association performance based on performance indicators in the form of quality,the quality is rather good. Based on performance indicators in the form ofquantity, the quantity is rather poor. Based on the performance indicators in theform of timeliness, the timeliness of The Association in completing the workincluding almost on time (rather good). Based on performance indicators in theform of effectiveness, the effectiveness is sufficient. Based on performanceindicators in the form of independence, the independence is sufficient.